2021
DOI: 10.1186/s12885-021-08178-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of nomograms for predicting axillary non-SLN metastases in breast cancer patients with 1–2 positive sentinel lymph node macro-metastases: a retrospective analysis of two independent cohorts

Abstract: Background It is reported that appropriately 50% of early breast cancer patients with 1–2 positive sentinel lymph node (SLN) micro-metastases could not benefit from axillary lymph node dissection (ALND) or breast-conserving surgery with whole breast irradiation. However, whether patients with 1–2 positive SLN macro-metastases could benefit from ALND remains unknown. The aim of our study was to develop and validate nomograms for assessing axillary non-SLN metastases in patients with 1–2 positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…extracapsular extension were independent risk factors for non-SLN metastasis. While some research has shown that non-SLN metastasis is associated with the number of tumor lesions in breast cancer, no association was observed in our study (8). In the MSKCC nomogram, the effect of ER status was only borderline significant (p = 0.08), but ER status was included in the MSKCC nomogram to improve the overall predictive capacity (4).…”
Section: Discussioncontrasting
confidence: 77%
“…extracapsular extension were independent risk factors for non-SLN metastasis. While some research has shown that non-SLN metastasis is associated with the number of tumor lesions in breast cancer, no association was observed in our study (8). In the MSKCC nomogram, the effect of ER status was only borderline significant (p = 0.08), but ER status was included in the MSKCC nomogram to improve the overall predictive capacity (4).…”
Section: Discussioncontrasting
confidence: 77%
“…Duplicate studies accounted for 516 of these exclusions, whereas screening titles and abstracts resulted in another 1114 exclusions. The full texts of 125 articles were evaluated and 25 studies met the inclusion criteria [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…China (n = 20), Turkey (n = 3), Italy (n = 1), and Japan (n = 1) were among the 25 included studies, with varying geographical locations and ethnic backgrounds. In addition, one study included two subgroup cohorts [ 21 ]. Table 1 presents the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al recently reported a nomogram based on the factors which included serum tumor markers such as CA 15–3 and CEA 14 . They demonstrated that the addition of CEA and CA15-3 significantly improved the discrimination ability of the nomogram compared to the nomogram without both serum markers.…”
Section: Discussionmentioning
confidence: 99%